The falls. Testament of love [videorecording (DVD)]. - Garcia, Jon; Farmer, Benjamin; Ferrucci, Nick; Barefoot, Hannah; Egan, Trish (Breaking Glass Pictures, 2013)
The sequel to The Falls picks up five years after the doomed romance between Mormon missionaries RJ and Chris. Though their lives have taken radically different paths, the death of a mutual friend reunites the two men at a time when both are attempting to establish adult lives. As old feelings of love and regret are rekindled, RJ and Chris must once again confront their seemingly impossible love. Will their reunion prove that they're fated to be together, or is it merely a temporary fantasy?